Understanding Exercise Intentions among Women Exercising in Fitness Classes: An Application of the Theory of Planned Behaviour - Krzysztof Sas-Nowosielski; Mirela Nowicka (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
The study was aimed at examining the usefulness of the Theory of Planned Behaviour (TPB) in predicting exercise intentions and exercise of women in fitness classes. On the theoretical plane it broadens state of knowledge on the TPB, but the findings are also important for the development of more effective interventions to promote and maintain exercise engagement of women in fitness centers. The study was carried out in the second quarter of 2016 in two fitness centers in Katowice, Poland. The participants were 95 women aged 17-66 (M=37.40±12.15). The obtained data were analyzed with the use of structural equation modelling (path analysis). Significant predictors of intention to exercise were perceived behavioural control and attitude, with the strongest effect observed in the former. The findings of the study suggest that interventions should focus on increasing the level of control over women's exercise behaviours and shaping attitudes toward them.